The Romance of Tristran by Beroul and Beroul II : A Diplomatic Edition and a Critical Edition - Beroul, active 12th century (Book collections on Project MUSE., 2015)
This volume is a comprehensive and up-to-date presentation of this story, including the first ever diplomatic edition of the text, replicating the exact state of the original manuscript.